Integration of multiple intelligence in the learning process of physical education in elementary school based on teacher gender - Ismail Gani; Tomoliyus Tomoliyus; Awan Hariono (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The purpose of this study is to determine elementary school physical education teachers' awareness of the integration of multiple intelligences in the learning process in terms of teacher gender. Multiple intelligence integration is made up of eight sub-variables: logical-mathematical, linguistic-verbal, visual-spatial, musical, body-kinesthetic, interpersonal, intrapersonal, and naturalist intelligence.This study is a comparative quantitative study. The participants in this study were elementary school physical education teachers from Special Region of Yogyakarta, Indonesia. The Simple Random Sampling system was used to collect samples, and 58 teachers agreed to participate, with 36 male teachers and 22 female teachers. Data was collected using a questionnaire instrument with 29 questions and a 5-point Likert scale answer. All question items were deemed reliable because their r-count value was greater than r-table 0.254. On Cronbach's alpha, each sub-variable tested for reliability is worth more than 0.6. For normally distributed and homogeneous data, independent sample t test analysis was used. The Mann-Whitney Test is used to identify data that does not meet the prerequisite test. According to the results of the Independent sample t test analysis, the significance value of each variable is as follows: mathematical logic (0.735 > 0.05), visual spatial (0.880 > 0.05), musical (0.045 < 0.05), and intrapersonal (0.637 > 0.05). The independent sample t test results show that there is no difference in teacher awareness of multiple intelligence integration (logical-mathematical, visual-spatial, intrapersonal) between male and female teachers. These findings also show that there are differences in teacher awareness in the integration of multiple intelligences (musical) between male and female teachers. The significance value of each variable based on the non-parametric test using the Mann-Whitney Test is as follows: linguistic verbal 0.443 > 0.05, body-kinesthetic 0.273 > 0.05, interpersonal 0.826 > 0.05, and naturalist 0.563 > 0.05. These findings show that there is no difference in teacher awareness of multiple intelligences (verbal-linguistic body-kinesthetic, interpersonal, naturalist) between male and female teachers. The findings of this study can be used by the curriculum sector, school principals, and other related organizations to facilitate physical education teachers, especially male teachers, in training the integration of multiple intelligences in the learning process. Based on the findings of this study, it is hoped that further research into the integration of multiple intelligences in physical education will be conducted.